Gambaran Tata Ruang Perpustakaan dalam Meningkatkan Minat Baca Mahasiswa di Perpustakaan Universitas Islam Riau - Gusti Mayasari; Lili Handayani; Hasnidar; Fera Yulia (Perpustakaan Universitas Riau, 2024)
The arrangement of a library room needs to be done carefully and consider various aspects. A well-organized library room will provide a comfortable atmosphere for library visitors so that they are interested in reading. The purpose of this research is to see the description of the existing spatial layout in the UIR library so that it can increase reading interest in the UIR library. This research uses descriptive qualitative method, using primary data sources and secondary data sources. The number of informants was 12 people. Indicators of this study are spatial layout (room layout, furniture, lighting, coloring and air circulation) and reading interest (facilities, environment and motivation). From the research results obtained that the management of library layout in the UIR library has been running well. This can be seen in terms of room arrangement using detailed spatial arrangement, effective and efficient arrangement and arrangement of tables and chairs according to the needs of visitors. For the arrangement of furniture in the UIR library by using bookshelves labeled and numbering instructions on each bookshelf and arranged neatly, Furthermore, the Lighting section in the UIR library utilizes LED lights and sunlight entering the library room while for wall coloring in the UIR library using Cream color and the last is air circulation in the UIR library using air conditioning (AC) and window ventilation system. With a good room arrangement and providing a sense of comfort has great potential to increase the reading interest of UIR library visitors